GEREJA DAN KETERLIBATANNYA DALAM DUNIA REFLEKSI PASTORAL ATAS GAUDIUM ET SPES - Mateus Mali (P3TK, Sanata Dharma University, 2013)
This article deals with Gaudium et Spes, pastoral constitution on the Church in modern World. Gaudium et Spes is the one most valuable result of the Second Vatican Council. Throughout this constitution, the Council highlights the church's willingness to be with the contemporary realm. The Council also wants to create an environment of dialogue, where the church would engage in all the forces of the modern world. The church must be involved in the world. Vatican II stirs the consciences of all Christians, reminding them of their solidarity, to fulfill the will and the prayer of Jesus Christ that all his followers be one, even as he and the Father are one (Cfr. GS 1).